2021
DOI: 10.1590/1676-0611-bn-2020-1122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urbanization on the fauna of Odonata on the coast of southern Brazil

Abstract: Urbanization significantly increases the rates of environmental disturbance, being one of the main causes of habitat loss and biodiversity. The growing trend of converting the natural landscape into areas for real estate speculation in the coastal region of the southernmost part of Brazil is a current concern, as the region is home to unique ecosystems, such as dunes, wetlands and large brackish lagoons. As they are organisms sensitive to environmental changes, variations in the structure of Odonata communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Habibullah et al (2022) indicated that climate vulnerability exacerbated habitat loss of endangered species due to increased deforestation, intense weather, and natural catastrophe. According to Sganzerla et al (2021), extensive urbanization exacerbates environmental and economic problems by causing an imbalance in resource management, increasing deforestation, harming biodiversity, and causing habitat loss for endangered species. According to Araujo et al (2021), expanding industrialization production and a lack of resource conservation policies increase habitat loss of endangered species and biodiversity loss, which requires sustainable ecological knowledge to safeguard natural resources by limiting deforestation and irresponsible production and consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Habibullah et al (2022) indicated that climate vulnerability exacerbated habitat loss of endangered species due to increased deforestation, intense weather, and natural catastrophe. According to Sganzerla et al (2021), extensive urbanization exacerbates environmental and economic problems by causing an imbalance in resource management, increasing deforestation, harming biodiversity, and causing habitat loss for endangered species. According to Araujo et al (2021), expanding industrialization production and a lack of resource conservation policies increase habitat loss of endangered species and biodiversity loss, which requires sustainable ecological knowledge to safeguard natural resources by limiting deforestation and irresponsible production and consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Also, due to either sensitivity or tolerance to environmental stressors, some species are considered to be indicator species of ecosystem health(Bybee et al, 2016;Lamelas-López et al, 2017;Nasirian & Irvine, 2017). For instance, an analysis bySganzerla et al (2021) revealed that two morphospecies found in our system: Erythrodiplax sp. and T. simulata, were strongly associated with non-urbanised areas.…”
mentioning
confidence: 95%
“…Modifications generated by land use, such as monoculture, livestock and urban areas, replace native vegetation by exotic species and impermeable surfaces (i.e., buildings), resulting in local microclimate change and other aquatic and terrestrial physicochemical characteristics of riparian zones (McKinney 2002, Wen et al 2017, Brasil et al 2021). These effects convert natural environments into areas with homogeneous biotic and abiotic characteristics that also affect the diversity and composition of odonates (Calvão et al 2018, Renner et al 2018, Borges et al 2021, Sganzerla et al 2021. In anthropic areas, sensitive species (e.g., some Zygoptera) are substituted by generalist groups with tolerant traits (e.g., multivoltine, r-strategist and heliothermic), often simplifying odonate communities (De Marco et al 2015, Dalzochio et al 2018b, Oliveira-Júnior & Juen 2019.…”
Section: Introductionmentioning
confidence: 99%